The Effect of TGT (Teams Games Tournament) Type Cooperative Learning Assisted by Wordwall on Student Learning Activity in Islamic Religious Education Subject at SD IT Al Ghazali - Dina Rahmawati; Mazrur, Mazrur; Mahmudah, Istiyati (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
In the current era, every educational institution is expected to implement innovations to prepare students with quality human resources. One effort that can be made is to create and innovate within classroom learning processes. This study aims to determine the effect of applying Teams Games Tournament (TGT)-type cooperative learning assisted by Wordwall on student learning activity. The research method used is a quasi-experimental design with the Nonequivalent Control Group Design model. The population and sample consisted of all third-grade students at SDIT Al Ghazali, Palangka Raya. Data were collected using test techniques, including pretests and posttests. The data analysis techniques used include calculating mean scores, testing data normality and homogeneity, and performing a two-sample t-test (Assuming Unequal Variance). The results show that the average pretest score of the experimental class was 61.17 with a standard deviation of 17.09, while the average posttest score increased to 89.70 with a standard deviation of 10.22. Based on the hypothesis test using the Welch test, the obtained p-value was 0.00467, which is smaller than the significance level of 0.05. It indicates a significant difference between the two sample groups, with the posttest average being higher. Additionally, an 82.35% increase in student learning activity was recorded. Therefore, the implementation of TGT-type cooperative learning, assisted by Wordwall, significantly enhances the learning activities of grade III students at SDIT Al Ghazali Palangka Raya.